2020
DOI: 10.3390/ijms21030887
|View full text |Cite
|
Sign up to set email alerts
|

Lipidated Analogs of the LL-37-Derived Peptide Fragment KR12—Structural Analysis, Surface-Active Properties and Antimicrobial Activity

Abstract: An increasing number of multidrug-resistant pathogens is a serious problem of modern medicine and new antibiotics are highly demanded. In this study, different n-alkyl acids (C2-C14) and aromatic acids (benzoic and trans-cinnamic) were conjugated to the N-terminus of KR12 amide. The effect of this modification on antimicrobial activity (ESKAPE bacteria and biofilm of Staphylococcus aureus) and cytotoxicity (human red blood cells and HaCaT cell line) was examined. The effect of lipophilic modifications on helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 74 publications
1
61
0
Order By: Relevance
“…The activity varied with fatty acid chain length, with C 8 chains displaying the highest activity and larger C 14 chains displaying lower activity due to self-assembly into large aggregates. Unfortunately, however, lipidation increased the cytotoxicity of the peptides proportional to carbon length [156], which is consistent with other reports [157]. Both the improved activity and increased aggregation of higher carbon chain tails agree with previous work on N-terminal lipidation [158].…”
Section: Alternatives: Internal Modification Of Ampssupporting
confidence: 92%
See 1 more Smart Citation
“…The activity varied with fatty acid chain length, with C 8 chains displaying the highest activity and larger C 14 chains displaying lower activity due to self-assembly into large aggregates. Unfortunately, however, lipidation increased the cytotoxicity of the peptides proportional to carbon length [156], which is consistent with other reports [157]. Both the improved activity and increased aggregation of higher carbon chain tails agree with previous work on N-terminal lipidation [158].…”
Section: Alternatives: Internal Modification Of Ampssupporting
confidence: 92%
“…By attaching fatty acid chains to the amine groups of lysine or N-terminus residues, lipidation can be harnessed to improve the activity of AMPs by improving their hydrophobic interactions with bacterial membranes [155]. Recently, Kamysz et al found that N-terminus conjugation of C 4 -C 14 fatty acid chains enhanced the activity of an alpha-helical LL-37 fragment against a variety of MDR pathogens [156]. The activity varied with fatty acid chain length, with C 8 chains displaying the highest activity and larger C 14 chains displaying lower activity due to self-assembly into large aggregates.…”
Section: Alternatives: Internal Modification Of Ampsmentioning
confidence: 99%
“…AMPs solutions were prepared fresh prior to each experiment by diluting the AMPs' mother solutions directly in the appropriate cell or bacteria culture medium. AMPs were tested at the concentrations detailed in Table 1, based on previously reported MIC values in literature for LL-37 (Overhage et al, 2008;Leszczynska et al, 2013;Luo et al, 2017;Saporito et al, 2018;Kamysz et al, 2020) and Nisin (Brumfitt et al, 2002;Piper et al, 2009;Dosler and Gerceker, 2011;Iancu et al, 2012;Shin et al, 2015).…”
Section: Antimicrobial Peptides (Amps)mentioning
confidence: 99%
“…Cells were directly seeded onto the wells of a 96 multiwell plate at a defined density (5x10 3 cells/well) and cultivated for 24 h (Brumfitt et al, 2002;Piper et al, 2009;Dosler and Gerceker, 2011;Iancu et al, 2012;Shin et al, 2015) LL-37 5, 7.5, 10, 25, 50, 75 1-50 (Overhage et al, 2008;Leszczynska et al, 2013;Luo et al, 2017;Saporito et al, 2018;Kamysz et al, 2020) to allow adhesion and spread. Next, Nisin or LL-37 peptides were added to each well according to the concentration stated in Table 1 by directly diluting mother solutions into the medium and incubated for 24 h in direct contact with cells.…”
Section: Metabolic Activity Evaluationmentioning
confidence: 99%
“…Several approaches have been used for extracting such information; isothermal titration calorimetry (ITC), bioinformatics simulations and NMR have revealed very precise information about AMP-membrane interactions [ 47 , 66 , 67 , 85 , 86 , 87 , 88 ]. For example, NMR has revealed interactions altering membrane curvature leading to its disruption for peptides such as those derived from magainin and LL-37 [ 9 , 10 , 88 , 89 , 90 ]. This indicated that additional studies with peptide 35409-1 are required to better understand its disposition on the membrane and the specific interactions taking place there, even though this study involved an initial approach to its mechanism of action on E. coli membrane.…”
Section: Discussionmentioning
confidence: 99%